Social learning and social design using ipads and groupware technologies - Mavri, Aekaterini; Ioannou, Andri; Loizides, Fernando; Souleles, Nicos (My University, 2018)
Over the past few years we have seen the uptake of the iPad into the Higher Education (HE) curriculum, in purpose of encouraging active social learning. This is augmented through direct-input interfaces, multi-touch interactions and portable, ubiquitous, formal and informal learning, aligning ably with the social constructivist model. Its widespread integration across multiple epistemological domains has been the subject of considerable research, yet more vertical and targeted understanding of its potential within specialized domains, used with typical context-specific software, is still in need. Its affordances for collaboration, a primary concept in higher education, rooted in the shift from individualistic to richer collective learning paradigms [1], also warrants further investigation. In this case study we examine the contribution of the iPad in a tertiary design course which focuses on User Experience (UX) design, a socially-aware collaborative design area. Through the collective activity of co-located and remote student dyads aiming to co-create artefacts such as sitemaps and mind maps, this study seeks to observe the impact of mobile devices on the students’ social learning process and perceived outcomes. The findings suggest and confirm the device’s ability to extend social learning beyond the classroom, its suitability and positive role, particularly in the early exploratory stages of the design lifecycle, as well as the necessity for promoting learner-autonomy particularly in the co-configuration of the software tools and peripheral equipment in order to suit the discipline-specific (UX design) and phase-specific activities.
Keywords: Collaborative learning; Social learning; Groupware; Usability; Courseware; Shared workspaces